Efektivitas Komunikasi Pemangku Adat Dalam Pencegahan Konflik Keagamaan Di Kecamatan Siporok Kabupaten Tapanuli Selatan - Latip Kahpi; Asriana Harahap (Hikmah, 2020)
AbstractThis study is a qualitative research,the method  of the study is descriptive interpretative methods, which describe and interpret what their research results. The Source of the data  are primary and secondary sources of data. The primary  source of dataisTraditional Leadersin the district of Sipirok, SouthTapanuli,  which consists of MangarajaTenggar, Sire Marduri, Mangaraja Hurning, Mangaraja Lintong, Sutan Soripada Parlindungan, Hamdan Siregar. Secondary sources of data is chairman of  KUA (Office of Religious Affairs in the district of  Sipirok), Akhirul Pane (MUI in the districts of Sipirok) Rev. A. Sinaga, and Rev. Maruli Hutagalung. The objective of research is to find out how the forms of communication of traditional leaders  in the prevention of religious conflicts in the district  Sipirok, to know the effectiveness of  forms of traditional leaders’communication. To know the obstacles and the implications of traditional leaders’ communication in the prevention of religious conflict in the district of Sipirok, South Tapanuli. The result of the research which  there are three forms of traditional leaders’ communication   in the prevention of religious conflicts, they are interpersonal communication, group communication, and communication that  using mass media. The obstacles of traditional leaders’ communication namely, internal and external obstacles. The internal obstacle is exclusive, traditional leaders is very  closed off to the public, and also there is  no room for the public to provide space and opportunity to express their opinions openly and freely. External obstacles include the occurrence of language differences especially with immigrant communities that cause misunderstanding between traditional leadership and the community.Keywords: Effectiveness, Indigenous Holders, and Religious Conflict.